The Application of Response Surface Methodology in the Study of Photodegraded Industrial Dairy Effluents by the Photo-Fenton Process: Optimization and Economic Viability. (19th February 2014) - Loures, Carla Cristina Almeida; Izário Filho, Hélcio José; Oliveira, Ivy dos Santos; Lamas Samanamud, Gisella Rossana; Souza, André Luiz de; Silva, Messias Borges
Abstract : This study presents results from an application of Photo-Fenton process for organic-load reduction in dairy effluents. Process efficiency was evaluated in terms of percentage dissolved organic carbon, chemical oxygen demand, and biochemical oxygen demand (DOC, COD, and BOD, resp.), whose initial values were 1658 ± 145  mg O2  L −1, 9500 ± 500  mg O2 L −1, and 2400  ±  100  mg O2  L −1, respectively. We applied a statistical design represented by Box-Behnken factorial design inclusive of Fenton's reagent, the power of applied radiation (W), and pH factors. The set temperature value was 30°C with a reaction time of 60 min. The maximum efficiency obtained was at p H = 3.5, Fenton reagent in the proportion of 35 g H2 O2  +  3.6 g Fe 2+, and ultraviolet radiation potency of 28 W. The results obtained for DOC, COD, and BOD were 81%, 90.7%, and 78.8%, respectively. Regarding the cost/benefit evaluation, the variables and their levels should be the following: pH 3.5, 35.0 g H2 O2 /Fe 2+ 3.6 g, and 28 W UV, obtaining a reduction in concentration of 79.5% DOC.